Computer Gaming Disorder and ADHD in Young Children—a Population-Based Study. - Paulus, Frank W.; Sinzig, Jenny; Mayer, Hannah; Weber, Monika; von Gontard, Alexander (International Journal of Mental Health & Addiction, 2018)
As new mass media has become a common activity already in nursery school, this study aimed to analyze computer game playing, addiction, and ADHD in a representative population-based sample of young children. Parents filled out a standardized questionnaire including items for ADHD, media use, and computer gaming disorder. The response rate was 83.2% (N = 1271). The mean age was 5.8 years (SD 0.38). Boys play computer games more often and longer than girls. In consequence, boys were rated more often to be at risk or to have a computer gaming disorder than girls. Children with elevated ADHD scores showed significantly higher computer gaming disorder scores. Clinically relevant inattention scores were associated with longer and more computer gaming. In a multiple regression analysis, problem game playing was best explained by a combination of frequency, gender, inattention, and hyperactivity-impulsivity score (p < .001; R = .305).